Rekultywacja gruntów pogórniczych w PGE KWB Turów S.A. = The reclamation of dumping grounds in PGE KWB Turów S.A. - Nietrzeba-Marcinonis, Jolanta (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The forest reclamation of dumping grounds in Turów since 60 years permitted on elaboration of own reclamation model. The ecological results are coming into being forest ecosystems about character a mixed highland forest with characteristic the arrangement of levels the diagnostic forest soils.
Keywords: rekultywacja o kierunku leśnym; grunty pogórnicze; forest reclamation; dumping groups